2014
DOI: 10.2215/cjn.09360913
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Urine Output Thresholds That Identify a Very High Risk of AKI in Patients with Septic Shock

Abstract: Background and objectives To promote early detection of AKI, recently proposed pretest probability models combine sub-Kidney Disease Improving Global Outcomes (KDIGO) AKI criteria with baseline AKI risk. The primary objective of this study was to determine sub-KDIGO thresholds that identify patients with septic shock at highest risk for AKI.Design, setting, participants, & measurements This was a retrospective analysis of 390 adult patients admitted to the medical intensive care unit (ICU) of a tertiary, acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 37 publications
(38 reference statements)
1
35
0
Order By: Relevance
“…The authors appreciate that hourly urine output can be a predictor of AKI or of impending requirement for acute RRT [26, 27]. It has variable sensitivity however, and the most encouraging of previous studies has suggested decreasing urinary output has an ROC of 0.7 for detecting AKI [28]. Thus, while urine output compares favourably to kGFR it has the disadvantage of requiring more intensive nursing and urine monitoring and with an intrinsic degree of unreliability in measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The authors appreciate that hourly urine output can be a predictor of AKI or of impending requirement for acute RRT [26, 27]. It has variable sensitivity however, and the most encouraging of previous studies has suggested decreasing urinary output has an ROC of 0.7 for detecting AKI [28]. Thus, while urine output compares favourably to kGFR it has the disadvantage of requiring more intensive nursing and urine monitoring and with an intrinsic degree of unreliability in measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prediction of AKI by urinary output varied by the patient cohort with the performance being better in medical than in surgical patients. In septic shock, a duration of at least 5 h, however, appears to be a good predictor of AKI [15]. Finally, Md Ralib et al [16] found a correlation between the volume of urinary output and duration of oliguria which suggested that a lower threshold of 0.3 ml/kg/h should be used, if the 6-hour observation interval is used as a minimum for the definition of stage of AKI.…”
Section: Oliguria As Biomarkermentioning
confidence: 99%
“…In the setting of AKI, decreases in urine output often precede increases in S cr . However, urine output still remains a less than ideal surrogate of renal function . Decreased urine flow rate may reflect hypovolemia without a corresponding decrease in GFR.…”
Section: Existing Renal Assessment Toolsmentioning
confidence: 99%